IMPROVING THE INTERROGATION OF CRIMES RELATED TO EXTREMISM BY THE BODIES OF INTERNAL AFFAIRS - Nurumbetova Sadokat Allayarovna (Scholars Digest Publishing, 2023)
The article analyzes the concept of distributing information and materials in any form, inspired by the ideas of religious extremism, separatism and fanaticism, inciting extermination or forced displacement of citizens, or aimed at creating panic among the population, as well as their role and importance in criminal legislation. In addition, the author’s opinion concerning the actions of people who are engaged in prohibited religious extremist activities using computer networks, deviating from the scope of the established rights and obligations, trying to violate the rules of the existing law in the society, the characteristics of the use of criminalistic ally important information in the fight against extremism in the bodies of internal affairs are expressed.
Keywords: social network, criminal prosecution, protection, security, religious extremism, separatism, bigotry, immunity, flyer, manual